'No jab, no job': the legal implications for employers. (2nd April 2021) - Bernstein, Adam
Abstract : Those on the health and social care frontline are largely aware of the benefits of vaccination, especially in relation to COVID-19. However, the legalities of linking vaccination status and employment are murky, even in the care sector. Adam Bernstein investigates.